2016
DOI: 10.7326/m16-0476
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Breast Cancer Screening Intervals by Breast Density and Risk for Women Aged 50 Years or Older: Collaborative Modeling of Screening Outcomes

Abstract: Background Biennial screening is generally recommended for average-risk women aged 50–74 years, but tailored screening may provide greater benefits. Objective To estimate outcomes for varying screening intervals after age 50 based on breast density and risk. Design Collaborative simulation modeling using national incidence, breast density, and screening performance data. Setting U.S. population. Patients Women ages ≥50 with combinations of breast density and relative risk (RR: 1.0, 1.3, 2.0, 4.0). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 50 publications
1
143
0
Order By: Relevance
“…These factors represent clinically available information that can and should be used by clinicians to stratify breast cancer risk for improved risk-based screening and primary and secondary prevention efforts. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors represent clinically available information that can and should be used by clinicians to stratify breast cancer risk for improved risk-based screening and primary and secondary prevention efforts. 4 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although it is impossible to determine the cause of breast cancer in any individual case, 3 easily assessed risk factors that explain a substantial proportion of incident breast cancers can be used to stratify breast cancer risk for targeted screening 4 and primary prevention 5 and improve public health interventions to reduce breast cancer risk.…”
mentioning
confidence: 99%
“…68 Biennial screening results in less benefit in terms of mortality reduction, but also fewer false-positive results, compared with the annual mammography in women aged 50 to 74 years. Screened and unscreened women both experience reductions in breast cancer mortality 911 implying that other factors (eg, cancer treatment) are also responsible for the reduced mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative modeling analyses indicate that biennial screening in women aged 50–74 years retained 78.2% of breast cancer mortality reduction of annual screening (25.8% reduction in biennial screening versus 33.0% reduction in annual screening compared with no screening), 84.5% of years of life gained of annual screening (122.4 years of life gained per 1,000 women screened by biennial screening versus 144.8 years by annual screening compared with no screening), and 86.4% of quality-adjusted life years (QALYs) gained of annual screening (86.0 QALYs gained per 1,000 women screened by biennial screening versus 99.5 QALYs by annual screening compared with no screening). 18,20 Multiple factors including trust in consensus guidelines, previously established screening patterns, physician financial incentives, and willingness to change preventive care patterns have prevented the full adoption of biennial screening recommendations. 11 Nevertheless, since the USPSTF screening guideline changes in 2009, annual mammography rates have declined significantly among U.S. adult women, 11,13,14 indicating at least some level of responsiveness to this guideline change.…”
Section: Discussionmentioning
confidence: 99%
“…1517 Collaborative models of breast cancer screening strategies suggested that a reduction in screening frequency would result in less benefit (mortality reduction) but also fewer false-positive results in the biennial mammography as compared with the annual mammography in women aged 50 to 74 years. 1820 …”
Section: Introductionmentioning
confidence: 99%